7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Opportunities and challenges in the application of Digital Twins for orchard management - Xiaojuan Liu; Leilei He; Shiao Niu; Rui Li; Yaqoob Majeed; Xiaoxu Sun; Jinyong Chen; Xiaojuan Li; Kerry Brian Walsh; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Deciphering microbial and metabolite dynamics in rice noodle fermentation: A metagenomic and untargeted metabolomic approach - Yuanyuan Ren; Yuhang Li; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Intensified rainfall overrides vegetation greening in driving erosion and carbon loss on the Tibetan Plateau - Rui Deng; Dongfeng Li; Yi Zhao; Desmond E. Walling; Panos Panagos; Pasquale Borrelli; Philippe Ciais; Yuefei Huang; Yuanyuan Bai; Sergey Chalov; Valentin N. Golosov; Xudong Fu; et al. (Science Bulletin, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Identification of a hypoxia-related gene signature associated with childhood asthma - Wenlie Chen; Yuanlu Huang; Li Lei; Rui Zhang; Li Fu; Jinwen Liao; Shaohua Wang; Zhenzhuang Zou (Genes & Genomics, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Deciphering the molecular mechanisms of oil palm lipid metabolism through combined metabolomics and transcriptomics - Jerome Jeyakumar John Martin; Wen Xu; Xinyu Li; Xiaoyu Liu; Lixia Zhou; Rui Li; Dengqiang Fu; Qihong Li; Hongxing Cao (Food Chemistry, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

Optimization Control of Flexible Power Supply System Applied to Offshore Wind–Solar Coupled Hydrogen Production - Lishan Ma; Rui Dong; Qiang Fu; Chunjie Wang; Xingmin Li (Journal of Marine Science and Engineering, 2025)
The inherent randomness and intermittency of offshore renewable energy sources, such as wind and solar power, pose significant challenges to the stable and secure operation of the power grid. These fluctuations directly affect the performance of grid-connected systems, particularly in terms of harmonic distortion and load response. This paper addresses these challenges by proposing a novel harmonic control strategy and load response optimization approach. An integrated three-winding transformer filter is designed to mitigate high-frequency harmonics, and a control strategy based on converter-side current feedback is implemented to enhance system stability. Furthermore, a hybrid PI-VPI control scheme, combined with feedback filtering, is employed to improve the system’s transient recovery capability under fluctuating load and generation conditions. Experimental results demonstrate that the proposed control algorithm, based on a transformer-oriented model, effectively suppresses low-order harmonic currents. In addition, the system exhibits strong anti-interference performance during sudden voltage and power variations, providing a reliable foundation for the modulation and optimization of offshore wind–solar coupled hydrogen production power supply systems.

Preparation and Characterization of Diclofenac Sodium-Purolite A430MR Complexes for Taste Masking - Genyang Ye; Qun Wang; Yibo Shang; Yibo Li; Rui Yang; Boyu Jing; Qiang Fu (AAPS PharmSciTech, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Reversing anther thermotolerance by manipulating the cis-elements in the promoter of a high-temperature upregulated gene Casein Kinase I in upland cotton - Yanlong Li; Yinuo Fu; Yaoyao Li; Rui Zhang; Jing Yang; Huanhuan Ma; Ling Min; Xianlong Zhang (Science China Life Sciences, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Advancements in artificial pollination of crops: from manual to autonomous - Leilei He; Xiaojuan Liu; Yusong Ding; Xudong Jing; Haojie Dang; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Spyros Fountas; Jayme Garcia Arnal Barbedo; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Growth characteristics based multi-class kiwifruit bud detection with overlap-partitioning algorithm for robotic thinning - Haojie Dang; Leilei He; Yufei Shi; Lamin L. Janneh; Xiaojuan Liu; Chi Chen; Rui Li; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Xiaoxi Kou; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Diurnal and seasonal variation of surface heat island of local climate zones using FengYun-4A land surface temperature data - Longteng Fu; Xian-Xiang Li; Rui Xin; Min Min; Lixin Dong (Urban Climate, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Observed response of microwave land surface emissivity to antecedent rainfall in Hainan Island - Jiawei Duan; Yuyun Fu; Jiheng Hu; Rui Li (International Journal of Remote Sensing, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)